YASHIL ARXITEKTURADAGI INNOVATSIYALAR: GLOBAL TENDENSIYALAR VA BARQAROR YECHIMLAR (KIUT Publication, 2025)
This article explores the latest advancements in green architecture, highlighting innovative technologies and design strategies that promote sustainability and environmental stewardship. From passive house designs to the integration of bio-based materials, these innovations are transforming the built environment and paving the way for a more sustainable future.